Length of cranial base and total face height in cephalograms for sex estimation in Indonesia - Ramadhani, Nabila Almira; Widyaningrum, Rini; Gracea, Rellyca Sola; Ningtyas, Aini Hasibah; Mudjosemedi, Munakhir (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: Sex estimation is the first step in identifying bodies following disasters or accidents. Craniometric analysis of lateral cephalograms can be used in the process. Among the measurements that can be used are the length of cranial base, determined by Basion–Nasion (Ba-N) length, and the total face height, determined by the Nasion–Menton (N-M) length, which can highlight significant differences between men and women. Purpose: This study aimed to determine the differences in length of cranial base and total face height measurements between men and women and to demonstrate how these two measurements can be used for sex estimation in the Indonesian population. Methods: This cross-sectional study employed a patient database from the dental hospital of Universitas Gadjah Mada. The study sample consisted of 116 cephalograms taken of 58 men and 58 women aged 20–40 years. The linear measurements were taken using EzDent-I Vatech software. Results: The mean cranial base length measurements in the men and women groups were 103.83 ± 4.37 and 96.01 ± 3.80 mm, respectively, whereas the total face height measurements were 121.03 ± 7.26 and 111.23 ± 5.09 mm, respectively. The Mann–Whitney U-Test revealed a significant difference (p < 0.05) between the groups. Logistic regression showed that the two measurements can be used to form an equation for sex estimation with an accuracy of 88.8%. Conclusion: Length of cranial base (Ba-N) and total face height (N-M) measurements from lateral cephalograms can accurately be used for sex estimation. Further research among specific populations is required to develop accurate methods for sex estimation employing morphometric examination on radiographs.